Social Innovation Through Tilapia Cage Culture in Tamansari Village, Banyuwangi - I Gede Eko Putra Sri Sentanu; Attabik Mukhammad Amrillah; Fery Widhiatmoko; Omar K. Burhan; Rumaisha Shalihah; Daffa Anggita Putri; Najdan Farizi; Riza Putra Achmad Danu; Daniel Rudolf Putra Manalib (Talenta Publisher, 2025)
This community service project aims to empower the youth of Karang Taruna in Tamansari Village, Banyuwangi, through social innovation in tilapia cage farming. The program seeks to enhance youth knowledge and skills in aquaculture, fostering greater productivity and community welfare. Through training and mentorship, the initiative aspires to develop an independent and competitive youth group capable of leveraging the village's potential in the fisheries sector. The project results show a positive impact, including increased capacity in institutional and aquaculture skills, the formation of the Pokdakan group, and the construction of nine tilapia cages in residential water channels.